ДЕЯКІ АСПЕКТИ ЗАСТОСУВАННЯ КОМП 'ЮТЕРНИХ ТЕХНОЛОГІЙ У ПРОЦЕСІ ВИВЧЕННЯ ДИСЦИПЛІНИ «ТЕХНІКА ГРАФІКИ» (Педагогіка вищої та середньої школи, 2007)
The article deals with the issues of computer technologies application while studying the course of «Graphics Techniques». The author comes to conclusion that using digital technologies gives better academic results in flexibility and variation, promotes a complex approach to studying, development of artistic thinking, a further development of students ' artistic consciousness. Computer technologies may promote the improvement of students' aesthetic taste, shape their artistic needs and an ability to self-realization and environment management by laws of beauty.